PERAN PEMERINTAH PROVINSI RIAU DALAM MENDORONG EKSPOR PRODUK KELOR UMKM (STUDI KASUS UPAYA DAPUR ARU EKSPOR) - Fahmi, Jihan Nabiila; Olivia, Yessi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the national economy by contributing 61% of total GDP and absorbing 97% of Indonesia's total workforce. Various efforts are made to empower MSMEs including export-oriented MSMEs. MSME empowerment is carried out by the central government and local governments in accordance with Law No. 20/2008. Empowerment is carried out because there are several obstacles in MSME exports. One of the regional MSMEs that has successfully exported officially is PT Mond Nature Lestari (Dapur Aru) after receiving assistance and empowerment from various parties. This research uses a qualitative method, by collecting primary data by interviewing MSMEs and government institutions and secondary data from several books, journal articles and websites. This research uses the theoretical framework of the role of government in encouraging MSMEs to export. This paper shows that the role of government in encouraging MSMEs to export has a division at each administrative level. The central government and local governments have their respective roles where the local government prepares and the central government processes. This research indicates that the Dapur Aru export process is assisted by the Riau Province Office of Trade, Industry, Cooperatives and SMEs. The Dapur Aru export process is a combination of central and regional empowerment programs. The use of the theoretical framework of the role of government in encouraging export MSMEs to the export process is correlative to the resolution of export constraints faced by MSMEs. Keywords: Government Role, Export, MSME Empowerment